NÍZAM ÚSTEMLIGI HÁM KORRUPCIYAǴA QARSÍ GÚRESIW – PUQARALÍQ JÁMIYETIN RAWAJLANDÍRÍWDÍŃ ÚSTEM SHÁRTI - Kudaybergenova, T.K. (SCIENCE and SOCIETY, 2023)
This article discusses the rule of law and the fight against corruption as a prerequisite for the development of society, the fight against corruption, its necessity and consequences.